An update on the role of the inflammasomes in the pathogenesis of kidney diseases - Darisipudi, Murthy N.; Knauf, Felix (Pediatric Nephrology, 2016)
Innate immune response pathways play a critical role as the first line of defense. Initiation of an immune response requires sensors that can detect noxious stimuli within the cellular microenvironment. Inflammasomes are signaling platforms that are assembled in response to both microbe-specific and nonmicrobial antigens. Upon activation, proinflammatory cytokines are released to engage immune defenses and to trigger an inflammatory cell death referred to as pyroptosis. The aim of this review is to provide an overview of the current knowledge of the role of the inflammasomes in the pathogenesis of kidney diseases. As crystal deposition in the kidney is a frequent cause of acute kidney injury and chronic kidney disease in children, recent insights into mechanisms of inflammasome activation by renal crystals are highlighted. This may be of particular interest to pediatric patients and nephrologists in need of new therapeutic approaches. Lastly, current data findings that inflammasomes are not only of major importance in host defense but are also a key regulator of the intestinal microbiota and the progression of systemic diseases are reviewed.
EVALuna2:3813